Accumulation of trace metals (Cd, Pb, Cu, Zn) in Arctic char ( Salvelinus alpinus ) from oligotrophic Alpine lakes: relation to alkalinity - Köck, G.; Hofer, R.; Wögrath, S. (Canadian Journal of Fisheries and Aquatic Sciences, 1995)
We studied Arctic char (Salvelinus alpinus) from five oligotrophic Alpine lakes in northern Tyrol, Austria, that differed in altitude (929–2796 m above sea level), pH (pH 5.4–8.3), and alkalinity (1.3–2750 μequiv.∙L −1 ). Concentrations of Cd, Pb, Zn, and Cu were measured in the water and in the kidney of fish, allowing the calculation of metal bioconcentration factors between water and fish kidney. Despite relatively low Cd and Pb concentrations in the water (Cd, 0.1 μg∙L −1 Pb, 0.5 μg∙L −1 , dissolved), metal concentrations in the kidneys of fish from the most acidic lake (Cd, 123 μg∙g −1 Pb, 19 μg∙g −1 , dry weight) were comparable with those of fish from waters polluted by direct discharge of metals. Concentrations of Cd and Pb in the kidney were negatively correlated with the alkalinity of the lakes. Comparison with data from other studies confirms the predictive utility of water alkalinity for estimating Cd accumulation in fish from oligotrophic lakes. The correlation between bioconcentration factors and alkalinity was negative for Cd and Pb, positive for Zn, and nonsignificant for Cu.